Transient Elastography in Alcoholic Liver Disease and Nonalcoholic Fatty Liver Disease: A Systemic Review and Meta-Analysis - Changzhou Cai; Xin Song; Xueyang Chen; Weihua Zhou; Qi Jin; Shenghui Chen; Feng Ji (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. Alcoholic liver disease (ALD) and nonalcoholic fatty liver disease (NAFLD) have become common chronic liver diseases. Recent evidence has shown the value of transient elastography (TE) in the context of ALD/NAFLD. The aim of this study is to investigate the accuracy of TE for diagnosing steatosis and fibrosis in ALD/NAFLD patients. Methods. We retrieved relevant English studies from the databases of PubMed, Embase, the Web of Science, and the Cochrane Library through March 31st 2019. We included studies regarding the diagnosis or staging of steatosis or fibrosis by using controlled attenuation parameter (CAP) or liver stiffness measurement (LSM) measured by TE in patients with ALD or NAFLD. The reference standard of all included studies was liver biopsy. A random-effects model was applied. Statistical analyses were performed using STATA. Results. A total of 62 articles were included and analyzed in our meta-analysis. In patients with ALD/NAFLD, the pooled results revealed that the sensitivity and specificity of CAP were 0.84, 0.83, and 0.78 and 0.83, 0.71, and 0.62 for steatosis grades ≥S1, ≥S2, and =S3, respectively. The sensitivity and specificity of LSM for identifying fibrosis grades ≥F1, ≥F2, ≥F3, and =F4 were 0.77, 0.77, 0.83, and 0.91 and 0.80, 0.82, 0.84, and 0.86, respectively. Conclusion. In patients with ALD/NAFLD, CAP was feasible for identifying and screening steatosis, and LSM was accurate for diagnosing fibrosis, especially severe fibrosis and cirrhosis.